2016
DOI: 10.1002/1873-3468.12278
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D prevents glycation of proteins: an in vitro study

Abstract: Human serum albumin (HSA) is an important protein involved in the transport of hormones, fatty acids, drugs, and other macromolecules. Under hyperglycemic conditions, this molecule undergoes irreversible modification that affects its structure and function. In this study, we explored the effect of two forms of vitamin D, a nutraceutical, on glycation modification in HSA. The protein was incubated with a physiologically high concentration of glucose in the presence of vitamin D metabolites. After 21 days, sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…The nonenzymatic glycation of lysine and arginine residues in HSA, in the case of diabetes, impairs the transport of several moieties leading to detrimental physiological effects. [ 37 ] Masking of the lysine and arginine residues has therefore been proposed as an effective strategy to inhibit nonenzymatic glycation of HSA. There are two main sites in the HSA structure which offer opportunities for drug action, Sudlow's Site I and Site II.…”
Section: Resultsmentioning
confidence: 99%
“…The nonenzymatic glycation of lysine and arginine residues in HSA, in the case of diabetes, impairs the transport of several moieties leading to detrimental physiological effects. [ 37 ] Masking of the lysine and arginine residues has therefore been proposed as an effective strategy to inhibit nonenzymatic glycation of HSA. There are two main sites in the HSA structure which offer opportunities for drug action, Sudlow's Site I and Site II.…”
Section: Resultsmentioning
confidence: 99%
“…Salum et al [ 18 ] recently found that oral administration of cholecalciferol led to a decrease of AGEs in the aortic wall of diabetic rats. Cholecalciferol and calcitriol prevented protein glycation in vitro [ 39 ]. Calcitriol may indirectly help with the clearance of AGEs through the kidney by protecting kidney structural integrity [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The samples were collected every 7 days for up to 28 days. For the evaluation of the antiglycation compound by using the electrochemical chip, a fixed concentration of 40 g/L BSA or 2% gelatin was incubated with the hyperglycemic concentration of glucose (300 mg/dL) and inhibitory concentration of aspirin (40 mmol/L) [9,26,34,[37][38][39]. To inhibit the growth of any microorganism, 1 mmol sodium azide was supplemented in all the solutions.…”
Section: Glycation Of Proteins and Evaluation Of Antiglycation Compoundmentioning
confidence: 99%
“…In 1983, the NBT reduction assay for evaluating glycation of protein was first introduced by Johnson et al [41]. The NBT is reduced by the ketoamine form of glycated protein, which causes a change in optical density at 525-530 nm [9,42]. Previously, the NBT assay was used to evaluate the level of glycation in albumin in the diabetic patients.…”
Section: Electrical Signal Measurements and Data Analysismentioning
confidence: 99%
See 1 more Smart Citation